Access to reading and redemption in Brazil: A critical analysis aimed at the UN 2030 agenda - Cinque, Yara Maria Silva [UNESP]; de Almeida, Carlos Cândido [UNESP] (University Library System, University of Pittsburgh, 2020)
Reading is an important mechanism for human development because it allows the individual to understand and interpret the world and the symbols that surround it. Thus, access must be for all people, not judging whether they are free or free. The reality of access and mediation of reading in Brazil faces problems due to the crisis in the prison system. Problems ranging from the lack of libraries to the lack of reading projects in all prisons. In the prison environment, the country still faces structural and political difficulties in making access to reading accessible to inmates even after 34 years of the Penal Enforcement Act (LEP) 7,210, dated 11 July 1984, for the creation of penitentiary libraries . There are only a few units that contain a library on their premises, such as the lack of proper professionals to operate on the premises. However, in order to have access to reading, education and work, the Brazilian State created the laws of redemption of punishment as a way of resocialization of the subject. The sentence to retrieve the reading was initiated by the Federal Penitentiary of Catanduvas, in the state of Paraná, where it was joined by other penitentiary institutions of federal scope. In 2013, the National Council of Justice (CNJ) conducted guidelines for the remission of sentences through reading. However, even with initiatives, there is still a gap between prisoners in access to reading and education. This research is of a bibliographical nature, in which a review of the literature and survey of the federal state legislations, as federal guidelines related to access to reading in penitentiary units, is carried out, in the accomplishment of the goals proposed by the United Nations Organization for Sustainable Development - Agenda 2030, mainly in objective 16. After the creation of the guidelines of the CNJ, some Brazilian states created their own laws of recovery of reading, other states decided to create only reading projects, so far there is no federal law related to the subject. We can not forget that the prison system and the public power are in crisis, in this sense, it is wrong to create expectations that only with the remission of prisoners will be re-socialized. In the same way, one should not create expectation in the Librarianship that until the moment does not have a literature that examines the redemption of the penalty from the perspective of the area.
Acesso à leitura e remição de pena no Brasil: Uma análise crítica visando a agenda 2030 da ONU
Keywords: Penalty remission; Reading access; Reading in prisons; UN Agenda 2030